2015
DOI: 10.1007/s13213-015-1126-x
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Muscodor vitigenus, M. equiseti and M. heveae sp. nov. in leaves of the rubber tree (Hevea brasiliensis Müll.Arg.), and their biocontrol potential

Abstract: Existence of Muscodor vitigenus, M. equiseti and M. heveae sp. nov. in leaves of the rubber tree (Hevea brasiliensis Müll.Arg.), and their biocontrol potential Abstract We isolated volatile metabolite-producing endophytic fungi from the leaves of the rubber tree (Hevea brasiliensis Müll.Arg.) and studied their antimicrobial competence. A total of three isolates was obtained, and their phenotypic and phylogenetic relationship with the genus Muscodor in the family Xylariaceae was studied. All isolates could prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
(58 reference statements)
0
10
0
1
Order By: Relevance
“…Over the course of exploration of endophytic fungal resources, a total of 21 Muscodor species were recorded to date: M. albus (Worapong et al., ), M. roseus (Worapong, Strobel, Daisy, & Castillo, ), M. vitigenus (Daisy et al., ), M. crispans (Mitchel, Strobel, Hess, Vargas, & Ezra, ), M. yucatanensis (Gonzalez et al., ), M. fengyangensis (Zhang et al., ), M. cinnamomi (Suwannarach, Bussaban, Hyde, & Lumyong, ), M. sutura (Kudalkar, Strobel, Riyaz‐Ul‐Hassan, Geary, & Sears, ), M. equiseti , M. musae , M. oryzae , and M. suthepensis (Suwannaracha et al., ), M. kashayum (Meshram, Kapoor, & Saxena, ), M. darjeelingensis (Saxena, Meshram, & Kapoor, ), M. strobelii (Meshram, Saxena, & Kapoor, ), M. heveae (Siri‐udom, Suwannarach, & Lumyong, ), M. indicus and M. ghoomensis (Meshram, Gupta, & Saxena, ), M. tigerii (Meshram, Gupta, & Saxena, ), M. coffeanum (Hongsanan et al., ), and M. camphorae (Meshram, Kapoor, Chopra, & Saxena, ). In a previous study of endophytic fungi from Oryza granulata collected from Xishuangbanna, southwest China, which is an area known to contain rich fungal biodiversity, we isolated two Muscodor strains (Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of exploration of endophytic fungal resources, a total of 21 Muscodor species were recorded to date: M. albus (Worapong et al., ), M. roseus (Worapong, Strobel, Daisy, & Castillo, ), M. vitigenus (Daisy et al., ), M. crispans (Mitchel, Strobel, Hess, Vargas, & Ezra, ), M. yucatanensis (Gonzalez et al., ), M. fengyangensis (Zhang et al., ), M. cinnamomi (Suwannarach, Bussaban, Hyde, & Lumyong, ), M. sutura (Kudalkar, Strobel, Riyaz‐Ul‐Hassan, Geary, & Sears, ), M. equiseti , M. musae , M. oryzae , and M. suthepensis (Suwannaracha et al., ), M. kashayum (Meshram, Kapoor, & Saxena, ), M. darjeelingensis (Saxena, Meshram, & Kapoor, ), M. strobelii (Meshram, Saxena, & Kapoor, ), M. heveae (Siri‐udom, Suwannarach, & Lumyong, ), M. indicus and M. ghoomensis (Meshram, Gupta, & Saxena, ), M. tigerii (Meshram, Gupta, & Saxena, ), M. coffeanum (Hongsanan et al., ), and M. camphorae (Meshram, Kapoor, Chopra, & Saxena, ). In a previous study of endophytic fungi from Oryza granulata collected from Xishuangbanna, southwest China, which is an area known to contain rich fungal biodiversity, we isolated two Muscodor strains (Yuan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A positive mycocidal or mycostatic effect similar to the effect of endophyte's volatile emission will confirm establishment of the endophyte and its mixture as the biocontrol or antifungal agent. (Meshram et al 2013(Meshram et al , 2017Suwannarach et al 2015;Saxena et al 2015;Suwannarach et al 2010Suwannarach et al , 2012Suwannarach et al , 2013Kudalkar et al 2012;Mitchell et al 2010;Worapong et al 2002;Daisy et al 2002;Siri-udom et al 2016…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…The VOCs produced by Muscodor cinnamomi CMU-Cib461 isolated from Cinnamomum bejolghota exhibited the potential to control tomato root rot caused by Rhizoctonia solani AG2 apart from promoting plant growth [24]. Another novel species, M. heveae, isolated from leaves of rubber tree elaborated VOCs which could effectively control root rot disease caused by Phellinus noxius and Rigidisporus microspores in rubber trees [25]. Furthermore, this group exclusively tested VOCs from M. heveae against white root rot disease in rubber tree and concluded that exploitation of VOCs of M. heveae would be an alternative method for controlling this major disease [26].…”
Section: Role Of Muscodor Spp In Crop Protectionmentioning
confidence: 99%